2017
DOI: 10.1253/circj.cj-16-1122
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Reduces the Risk of Worsening Renal Function in Patients With Acute Decompensated Heart Failure and Preserved Left Ventricular Ejection Fraction ― Prospective Randomized Controlled Study ―

Abstract: Background: Although the mainstay of treatment for acute decompensated heart failure (ADHF) is decongestion by diuretic therapy, it is often associated with worsening renal function (WRF). The effect of tolvaptan, a selective V2 receptor antagonist, on WRF in ADHF patients with preserved left ventricular ejection fraction (LVEF) is unknown. Methods and Results:We enrolled 50 consecutive ADHF patients whose LVEF on admission was ≥45%. Patients were randomly assigned to either tolvaptan add-on (n=26) or conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…10,25 Although effective renoprotective strategies in the early stage of AHF have not been fully determined, several prospective studies have shown that the aquaresis effect of tolvaptan, which is a vasopressin type 2 receptor antagonist with electrolyte-free water diuretic properties, inhibits intravascular hypovolaemia and subsequent incidence of WRF. 5,7,8,26 In patients with AHF, Shirakabe et al reported that tolvaptan significantly reduced the incidence of WRF and had a better mid-term cardiovascular outcome than furosemide. 5 However, these studies highlighted the effect of tolvaptan in patients with an advanced stage of AHF who were already receiving a high dose of furosemide (over 40 mg/day furosemide) before admission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,25 Although effective renoprotective strategies in the early stage of AHF have not been fully determined, several prospective studies have shown that the aquaresis effect of tolvaptan, which is a vasopressin type 2 receptor antagonist with electrolyte-free water diuretic properties, inhibits intravascular hypovolaemia and subsequent incidence of WRF. 5,7,8,26 In patients with AHF, Shirakabe et al reported that tolvaptan significantly reduced the incidence of WRF and had a better mid-term cardiovascular outcome than furosemide. 5 However, these studies highlighted the effect of tolvaptan in patients with an advanced stage of AHF who were already receiving a high dose of furosemide (over 40 mg/day furosemide) before admission.…”
Section: Discussionmentioning
confidence: 99%
“…Only two small clinical studies elucidated the effect of tolvaptan in preventing WRF in AHF based on left ventricular systolic function. 8,26 Although a favourable effect of tolvaptan in preventing WRF in patients with preserved ejection fraction has been reported, the effect of tolvaptan in preventing WRF in patients with reduced left ventricular systolic function has not been established. In our patients with new-onset AHF, tolvaptan add-on therapy demonstrated a more favourable effect in preventing WRF in patients with left ventricular systolic dysfunction and renal impairment compared with furosemide therapy on admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that we might avoid progressive hypochloremia by adjusting loop diuretics dose or replacing thiazides with other diuretics such as tolvaptan, which does not induce RAAS activation. [26][27][28] Serum chloride could be lowered as a result of anti-HF therapy such as diuretics, and hypochloremia might play a role as a severity marker of HF in ADHF patients. 19,29 Several parameters in this study, such as low blood pressure, serum BUN, sodium and chloride on admission, were associated with hypochloremia at discharge on logistic regression analysis, and were associated with poor prognosis in ADHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that responders to TLV in heart failure patients had a signi cant increase in urine volume soon after administration and improved clinical course with signi cant weight loss 23 . As similar to the previous studies, our study demonstrated that weight loss was also signi cantly related to the increase of urine volume at day 1 in nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 90%